2014
DOI: 10.1155/2014/605828
|View full text |Cite
|
Sign up to set email alerts
|

Hearing and Neurological Impairment in Children with History of Exchange Transfusion for Neonatal Hyperbilirubinemia

Abstract: The objective was to determine frequency of sensorineural hearing loss (SNHL), identified by abnormal threshold in evoked potentials, absence of otoacoustic emissions and behavioral responses, auditory neuropathy (AN) (absence of evoked potentials, with preservation of otoacoustic emissions), and neurological comorbidity in infants with hyperbilirubinemia (HB) treated with exchange-transfusion (ET). From a total of 7,219 infants, ET was performed on 336 (4.6%). Inclusion criteria were fulfilled in 102; 234 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…However, in this study, there was no relationship between peak TB levels and ANSD, whereas a correlation was found in another study of >600 subjects [47]. Similarly, Martínez-Cruz et al [48] found that, of 102 children who underwent exchange transfusion for hyperbilirubinemia, 15% presented with sensorineural hearing loss by a mean age of 5.5 ± 3.9 years; they also had a higher unconjugated bilirubin level than their peers without hearing loss. Hearing loss at the time of documented hyperbilirubinemia (defined as TB >10-20 mg/dL, depending upon the study) was diagnosed by ABR or an automated ABR (AABR) in 9.0-73.3% of children [46,4952], although the prevalence of hearing loss later in life (at 2 months to 2 years of age) was only 2-6.7% [5254].…”
Section: Introductioncontrasting
confidence: 53%
“…However, in this study, there was no relationship between peak TB levels and ANSD, whereas a correlation was found in another study of >600 subjects [47]. Similarly, Martínez-Cruz et al [48] found that, of 102 children who underwent exchange transfusion for hyperbilirubinemia, 15% presented with sensorineural hearing loss by a mean age of 5.5 ± 3.9 years; they also had a higher unconjugated bilirubin level than their peers without hearing loss. Hearing loss at the time of documented hyperbilirubinemia (defined as TB >10-20 mg/dL, depending upon the study) was diagnosed by ABR or an automated ABR (AABR) in 9.0-73.3% of children [46,4952], although the prevalence of hearing loss later in life (at 2 months to 2 years of age) was only 2-6.7% [5254].…”
Section: Introductioncontrasting
confidence: 53%
“…An increased risk of neurologic sequel was observed in children with SNHL. 24 In this case, exchange transfusion was done to the patient and the baby discharged home in good condition. A follow up for hearing impairment and development was scheduled to monitor longterm outcome.…”
Section: Discussionmentioning
confidence: 93%
“…According to several largescale studies on the subject, hyperbilirubinemia is generally accepted to be an important risk factor for congenital hearing loss. 17,18 Among those who did not receive any potentially ototoxic medication, 94.6% had a PASS result and 5.4% had a REFER result (3.6% for one ear, 1.8% for both ears), while among those who received potentially ototoxic medication (aminoglycosides and loop diuretics), only 76.9% had a PASS result and 23.1% had a REFER result (13.9% for one ear, 9.3% for both ears), the difference proving to be statistically significant (p <0.001).…”
Section: Case Series Presentationmentioning
confidence: 99%